2013
DOI: 10.1155/2013/874367
|View full text |Cite
|
Sign up to set email alerts
|

The Effects ofN-Butyl-1-(4-dimethylamino)phenyl-1,2,3,4-tetrahydro-β-carboline-3-carboxamide againstLeishmania amazonensisAre Mediated by Mitochondrial Dysfunction

Abstract: Leishmaniasis is a disease that affects millions of people worldwide. The drugs that are available for the treatment of this infection exhibit high toxicity and various side effects. Several studies have focused on the development of new chemotherapeutic agents that are less toxic and more effective against trypanosomatids. We investigated the effects of N-butyl-1-(4-dimethylamino)phenyl-1,2,3,4-tetrahydro-β-carboline-3-carboxamide (C4) and its possible targets against L. amazonensis. The results showed morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Considering that trypanosomatids have only one mitochondrion, such an organelle may be considered a potential therapeutic target (44). Several studies have reported that different classes of compounds (40,(45)(46)(47), including quinoxaline derivatives (27), cause mitochondrial dysfunction in trypanosomatids.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that trypanosomatids have only one mitochondrion, such an organelle may be considered a potential therapeutic target (44). Several studies have reported that different classes of compounds (40,(45)(46)(47), including quinoxaline derivatives (27), cause mitochondrial dysfunction in trypanosomatids.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it was also active against axenic and intracel- lular amastigote forms, exhibiting high selectivity for the parasite, independent of the evolutive form assessed. Furthermore, ␤-CB presented more pronounced antileishmanial activity than another ␤-carboline compound presenting the N-butylcarboxamide group, N-butyl-1-(4-dimethylamino)phenyl-1,2,3,4-tetrahydro-␤-carboline-3-carboxamide, against the same species and evolutive form (11). However, its activity was slightly lower than a similar compound possessing an N-benzylcarboxamide in place of the N-butylcarboxamide group (12).…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have sought to develop new treatment alternatives for leishmaniasis. ␤-Carboline compounds, characterized by a tricyclic pyrido [3,4-b]indole ring structure, have been evaluated as potential antileishmanial molecules (8,11,12). In the present study, we evaluated the activity of the ␤-carboline compound ␤-CB against L. amazonensis, which causes cutaneous and diffuse cutaneous forms of leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations